2015
DOI: 10.1109/tmtt.2015.2446483
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Electrical Property Retrieval by Applying the Finite-Element Method (FEM)

Abstract: In this study, the finite-element method is applied to reconstruct the electrical properties (conductivity and permittivity) maps of media with 1-D, 2-D, and 3-D inhomogeneities based on the RF magnetic field distributions in a magnetic resonance imaging (MRI) system. The proposed method handles the discontinuity of electrical properties well. It therefore shows high accuracy at the boundary compared to retrieval methods in the literature. The method has successfully been validated using both analytical and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For example, Homann et al 8 reported a computation time of 45 minutes per Tx channel (eight channels) using a Finite Difference Time Domain (FDTD) solver. Other methods have been proposed for real-time assessment of an individual's local SAR, including approaches based on Electrical Properties Tomography (EPT), [30][31][32][33][34][35][36][37][38][39][40] Global Maxwell Tomography, [41][42][43] and thermoacoustic imaging. 44 However, these methods present other challenges in the accurate and timely calculation of local SAR distributions and are not widely used.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Homann et al 8 reported a computation time of 45 minutes per Tx channel (eight channels) using a Finite Difference Time Domain (FDTD) solver. Other methods have been proposed for real-time assessment of an individual's local SAR, including approaches based on Electrical Properties Tomography (EPT), [30][31][32][33][34][35][36][37][38][39][40] Global Maxwell Tomography, [41][42][43] and thermoacoustic imaging. 44 However, these methods present other challenges in the accurate and timely calculation of local SAR distributions and are not widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al and Zhang et al extended MR–EPT to the case of multiple transmit coils and incorporated the effective receive fields into their algorithm [14], [15]. Huang et al incorporated finite–element discretization in their MR–EPT implementation to improve conditioning [16], whereas Michel et al proposed a nonlinear filter to denoise b1+ maps prior to MR–EPT in order to reduce reconstruction errors [17]. Wan et al, Lee at al., and Marqués et al proposed versions of MR–EPT that use receive sensitivities (b1), which are simpler to measure and usually have higher SNR than b1+, to estimate EP [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Sodickson et al proposed the first differential technique free of any assumptions, dubbed Local Maxwell Tomography, which uses both transmit and receive fields from multiple RF coils to reconstruct EP on a voxel–by– voxel basis [25]. Various multi–modal approaches have also been proposed, usually combining MR–EPT with electrical impedance tomography (EIT), which is an invasive method [26], [27], [16], [28]. While most techniques reconstruct EP directly, some recently proposed differential techniques are implemented with iterative reconstruction schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Hafalir et al ( 25 ) then named this method as convection–reaction MREPT (cr-MREPT), as its governing equation is similar to the convection–reaction equation ( 26 ). The first-order PDE was then solved by Hafalir et al ( 25 ) for 2-dimensional reconstruction using a strong form with finite element method (FEM) ( 27 ). An obvious artifact was observed in the region where the gradient of is close to zero.…”
Section: Introductionmentioning
confidence: 99%